(untitled) (Research, Society and Development, 2022)
This study focused on the low-cost production of biosurfactant by Bacillus subtilis UCP 0999, using cassava wastewater (CWW) and waste frying oil (WFO) as renewable substrates. A 22 full-factorial design (FFD) was employed to investigate the effects of concentrations of agro-industrial wastes in surface tension (ST) and emulsification index (EI24). According to the results, the minimum value of ST (33.2 mN/m) and the maximum value of EI24 (95%) was obtained at central point of the FFD, using 5% CWW and 2% WFO. Statistical analyses demonstrated the significative influence of both substrates in ST and EI24. The biosurfactant showed 2.67 g/L yield and anionic and lipopeptide nature by Zeta potential and Fourier transform infrared (FT-IR) spectroscopy, respectively. In addition, promising applications of biosurfactant as biodispersant and viscosity reducing agent were demonstrated, suggesting its potential use in petroleum industry or bioremediation of hydrophobic pollutants.